ANALYSIS SHARIA FINANCIAL LITERACY OF KUALASIMPANG CITY COMMUNITY IN THE DIGITAL ERA - Dayyan, Muhammad; Mansyur (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2023)
In the digital era, people are increasingly familiar with social media. This study aims to determine the effect of income, socio-economic status and social media on Islamic financial literacy of the people in Kota Kualasimpang District. This study used a quantitative method with data collection instruments through questionnaires. The sample used was 99 respondents who were the people of the Kualasimpang City District. The data analysis technique used consisted of multiple linear regression equations, coefficient of determination test, F test and t test. The research results obtained on the income variable with a coefficient of 0.147, socio-economic status variable with a coefficient of 0.398 and social media with a coefficient of 0.458, thus the value of income, socio-economic status and social media have a positive effect on financial literacy. The results of the t test on the income variable with a t sig value of 2.194, the socio-economic status variable with a t sig value of 5.447 and social media with a t sig value of 6.315, meaning that partially income, socio-economic status and social media have a significant effect on financial literacy. The results of the F test obtained the value of F count > F table (51.615> 2.70) meaning that simultaneously income, socio-economic status and social media have a significant effect on financial literacy. The test results for the coefficient of determination were obtained at 0.608 or 60.8% income, socio-economic status and social media affect financial literacy.